The spectacle of criminal justice : mass media and the criminal trial - Smith, Rosie (Emerald Publishing Limited, 2022)
In a world defined by and lived through media spectacle, nearly every part of human existence can now be documented, watched, and scrutinised. When mass media has the power to make the mundane not only visible but also entertaining, how have issues surrounding criminal justice, crime, and death taken centre stage in this media-saturated social world? Presenting for the first time in a published work the concept of Spectacular Justice, which was developed during the author's doctoral research, Smith delves into how institutions of justice, such as criminal trials, as well as public expressions of justice, such as rage and grief, are played out in the media. Using media archival data, this book examines four murder case studies to develop a conceptual toolkit, designed to help the reader make sense of the complex position of justice in the spotlight. Taking the cases of Charles Lindbergh Jr, James Bulger, Jodi Arias, and Anders Breivik, Smith examines each through the lens of three key characters (Victim, Perpetrator, and Expert), and explores how human stories contribute both to the visibility of the case, and the thriving of justice spectacle. Highlighting the value of bridging the disciplinary divide between criminology and death studies, this book also demonstrates how spectacular justice is often most conspicuous at the intersection between crime and death. It is appealing reading for scholars interested in Criminology, Sociology, Death studies, and Media.